Pengaruh Employer Attractiveness dan Use of Social Media terhadap Intention to Apply Generasi Z pada PT XYZ Bandung - Aisna Dewi Romizza; Ratih Purbasari; Dian Fordian (Concept: Journal of Social Humanities and Education, 2026)
Competition to attract young talent in the digital era encourages companies to strengthen their Employer Attractiveness while also using social media as a recruitment communication channel. This study examines the effect of Employer Attractiveness and Use of Social Media on Generation Z's Intention to Apply at Company X, a food and beverage (F&B) company in Bandung. The study was motivated by a three-year decline in the number of job applications received by the company. A quantitative approach with a verificative survey design was employed. Data were collected from 97 Generation Z respondents who were familiar with the company through social media, selected using purposive sampling, and analysed with multiple linear regression supported by the F-test, t-test, and coefficient of determination. The results show that Employer Attractiveness and Use of Social Media each have a positive and significant effect on Intention to Apply, both partially and simultaneously, with Employer Attractiveness exerting a stronger influence than Use of Social Media. Together, the two variables explain 69.6% of the variance in Intention to Apply. These findings suggest that strengthening a company's image as an employer, supported by effective social media management, can increase Generation Z's Intention to Apply for jobs at Company X.